Journal of the International AIDS Society
Journal of the International AIDS Society, an official journal of the Society, provides an open access forum for essential and innovative HIV/AIDS research. Submission of research carried out by investigators in low- and middle-income countries is strongly encouraged. The emerging field of operations research can provide valuable information on various algorithms for monitoring and providing support for comprehensive yet affordable and sustainable treatment, prevention and care programmes for different contexts. Journal of the International AIDS Society will give higher priority to publications in this area of research. Topical areas include, but are not limited to: Basic and biomedical sciences, Behavioural sciences and epidemiology, Clinical sciences, Health economics and health policy, Operations and implementation research, Social sciences and humanities (including political sciences and media), Editorials, commentaries and discussion highlights from International AIDS conferences and other relevant conferences.--About page.